Liquid Metal Strain Gage To Test Cervical Facet Capsule Strain - Haibin CHEN; Yi WANG; Liying ZHANG; Guangyu YANG; Xin NING; Xuemei CHENG; Zhengguo WANG (Institute of Advanced Engineering and Science, 2013)
A broad range of investigations has been carried out to suggest that the facet joint capsule is a source of neck pain and the pain may arise from large strain in the joint capsule that will cause pain receptors to fire. To in vivo measuring cervical facet capsule strain, a special liquid metal was selected as a sensing element to develop a high-range miniature wire strain gage. The calibration tests and a sled rear-end impact experiment were carried out to examine the technical behavior of this strain gage. It is shown that: This strain gage has a relatively high strain range and a relatively high degree of linearity. Due to a miniature wire structure and a relatively high degree of flexibility of use as well as a minimal external adhesive force, this strain gage has the capability of in vivo testing cervical facet capsule strain. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1922